The Influence of Ethnoscience-Technology-based Science Instructional Design on the Learning Interest of Junior High School Students in Nagekeo Regency - Yohanes Freadyanus Kasi; Ari Widodo; Achmad Samsudin; Riandi Riandi; Ari Syahidul Shidiq (Universitas Sebelas Maret, 2026)
Current educational issues center on technology, cultural integration, and the challenge of equity. The primary focus is how to cultivate a generation of critical, digitally literate individuals while preserving local moral values amidst the onslaught of global culture. The purpose of this study is to analyze the effect of science instructional designs based on ethnoscience-technology on the learning interests of junior high school students in Nagekeo district. This research uses quantitative methods to analyze teachers' abilities to design ethnoscience-technology-based instructional designs and students' learning interests when taught by teachers. The participants were science teachers and students at junior high schools in Nagekeo District, NTT. Data collection techniques used questionnaires and observation sheets and analysis used quantitative descriptive and correlation analysis. The results show that teachers have linked the science material taught with cultural activities in Nagekeo district and included technology (ethnoscience-technology). Furthermore, there is a very strong and significant positive relationship between the quality of science teacher's instructional designs based on ethnoscience-technology and the learning interest of junior high school students in Nagekeo Regency with r=0.981. The conclusion of this research explains that science teachers in Nagekeo district have designed ethnoscience-technology based science instruction and it correlates with students' learning interests